Effects of Eleclazine (GS6615) on the proarrhythmic electrophysiological changes induced by myocardial stretch - Chorro, Francisco J.; Such-Miquel, Luis; Cuñat, Samuel; Arias-Mutis, Oscar; Genovés, Patricia; Zarzoso, Manuel; Alberola, Antonio; Such-Belenguer, Luis; Del Canto, Irene (Frontiers in Physiology, 2025)
PurposeMyocardial stretch is a proarrhythmic factor. Eleclazine (GS6615) is a late sodium current (INaL) inhibitor that has shown protective effects against arrhythmias in various experimental models. Data on its effects during myocardial stretch are lacking. The aim of this study was to investigate the electrophysiological modifications induced by eleclazine basally and during acute ventricular stretch.MethodsLeft ventricular stretch was induced at baseline and during perfusion with eleclazine in 26 Langendorff rabbit heart preparations. Programmed stimulation and high-resolution mapping techniques were applied using multiple epicardial electrodes.ResultsAt baseline, both the ventricular refractory period measured at a fixed cycle length (250 m) and its surrogate obtained during ventricular fibrillation (VF) decreased significantly during stretch (baseline 128 ± 15 vs. stretch 110 ± 14 m; n = 15; p < 0.001, and baseline 52 ± 13 vs. stretch 44 ± 9 m; n = 11; p < 0.05), while the VF dominant frequency (DF) increased significantly (DF baseline 13 ± 3 vs. stretch 17 ± 5Hz; n = 11; p < 0.01). Eleclazine 1.4 μM prolonged refractoriness, diminished both DF and conduction velocity during the arrhythmia, and avoided the stretch induced variations in refractoriness (baseline 148 ± 19 vs. stretch 150 ± 23 m; n = 15; ns, and baseline 73 ± 15 vs. stretch 77 ± 15 m; n = 11; ns) and in DF (baseline 12 ± 5 vs. stretch 12 ± 3 Hz; ns). The VF complexity index was inversely related to refractoriness (r = −0.64; p < 0.001). Under eleclazine perfusion, the VF activation patterns were less complex, and the arrhythmia stopped in 6 out of 11 experiments (55%; p < 0.05 vs. baseline).ConclusionEleclazine (GS6615) reduced the proarrhythmic electrophysiological changes induced by myocardial stretch and slowed and simplified activation patterns during VF in the experimental model used.